A transmit–receive array for brain imaging with a high‐performance gradient insert. Issue 4 (8th May 2020) - Rösler, Manuela B.; Leussler, Christoph; Brunner, David O.; Schmid, Thomas; Hennel, Franciszek; Luechinger, Roger; Weiger, Markus; Pruessmann, Klaas P.
Abstract : Purpose: The aim of this work was to provide parallel imaging capability for the human head in a gradient insert of 33‐cm inner diameter within the related constraints of space, encoding ambiguity, and eddy current immunity. Methods: Eddy current behavior of the 8‐channel transmit–receive array coil was investigated via heating and field deviation measurements. RF performance was evaluated using S‐parameters, noise statistics, B 1 maps, and g‐factor maps. In vivo images of a human head and knee were acquired with Cartesian readout and TE below 0.45 ms. Results: Under intense gradient use, the shield was heated up to 55°C and other coil structures to 40°C. After standard preemphasis calibration, eddy current‐related field distortions caused by the developed RF coil were smaller than for a commercial receive‐only coil. In the ambiguous regions of the gradient, B 1 + is 20 dB lower than in the center of the FOV. Coupling between elements is below −15 dB, and noise correlation is less than 0.31 when the coil is loaded with a head. Power efficiency was 0.52 ± 0.02 μT/√W, and the SD of the flip angle was below 10% in central slices of the brain. 2D, up to fourfold acceleration causes less than 30% noise amplification. The RF coil can be used during full gradient performance. Conclusion: Based on the described features, the presented coil enables parallel imaging in the high‐performance gradient insert.